2008
DOI: 10.3136/fstr.14.183
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Properties and Taste Compounds of Fermented Milk Produced by Lactococcus lactis and Streptococcus thermophilus

Abstract: The aim of this study was to characterize the sensory properties and taste compounds of the fermented milk (FM) produced by two species of lactic acid bacteria, Lactococcus lactis and Streptococcus thermophilus for 16 hours, and to compare them with those of yogurt (YG) made from the same reconstituted milk by Lactobacillus bulgaricus and S. thermophilus. Sensory evaluation showed that the sourness of FM was signifi cantly weaker than that of YG, and that the lactic acid content of FM was signifi cantly smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
2
13
1
1
Order By: Relevance
“…A total of 29 amino acids were identified and quantified here, more than in other studies (Gambelli et al 1999;Ott et al 2000;Omaea et al 2008), though the levels recorded were similar except for Lys, Thr and Cys. Rao et al (1982) reported higher levels of free Lys in milk fermented using L. bulgaricus, and Güzel-Seydim et al (2003) found Lys levels on the order of 8% of the total amino acids in yoghurt and kefir, much lower than the levels found here.…”
Section: Discussionmentioning
confidence: 57%
“…A total of 29 amino acids were identified and quantified here, more than in other studies (Gambelli et al 1999;Ott et al 2000;Omaea et al 2008), though the levels recorded were similar except for Lys, Thr and Cys. Rao et al (1982) reported higher levels of free Lys in milk fermented using L. bulgaricus, and Güzel-Seydim et al (2003) found Lys levels on the order of 8% of the total amino acids in yoghurt and kefir, much lower than the levels found here.…”
Section: Discussionmentioning
confidence: 57%
“…The main products of milk fermentation are organic compounds. Organic acids and carbonyl compounds enhance the sensory properties of yogurt (Tamime, 2006), and acidity and aroma are important quality aspects (Omae et al, 2008). Organic acids occur in yogurt because of bacterial activity and they contribute to the organoleptic characteristics.…”
Section: Acidity and Organic Acids In Yogurtmentioning
confidence: 99%
“…Locally produced yogurts in Africa have been shown to contain significant levels of lactococci 28 such as L. lactis, which can cause the production of peptides that have a bitter flavor [29][30][31][32] , which is generally undesirable 31 . Therefore, it is critical that fermentation takes place at an temperature between 45 and 35 °C 15,28 .…”
Section: Discussionmentioning
confidence: 99%